Enhancing ZIS management through marketplace platforms: Opportunities and sharia compliance challenges - Syarifuddin; Zaerofi, Afif (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Zakat Institutions and marketplace platforms have established a collaboration to adapt to the growing shift toward digital transaction patterns in managing Zakat, Infaq, and Shadaqah (ZIS). Marketplaces offer convenience in ZIS collection, while LAZ ensures Sharia compliance in fund management. This study highlights how such collaboration significantly expands the reach of ZIS collection, presenting immense potential, but also identifies challenges in ensuring Sharia compliance and accountability. The research employs a qualitative methodology to explore the dynamics of the collaboration between Zakat Institutions and marketplace platforms. Thematic analysis was applied to identify key themes related to the opportunities and challenges of the collaboration. The research contributes to the understanding of digital platforms' role in faith-based financial management, offering practical insights for enhancing cooperation between LAZ and marketplaces. It emphasizes the need for dialogue, public education about ZIS and qurban, and system adjustments to ensure Sharia compliance. The findings have practical implications for improving digital ZIS management through enhanced accountability and regulatory frameworks, making this collaboration a model for leveraging technology in religious fund management